Statistical Analysis of Obstetric Complications A Hospital Based Data in WadMedani Obstetrics and Gynecology Hospital, Gezira State, Sudan (2017) - Mohamed, Fatima A; Alnory, Ahmed (Edelweiss Applied Science and Technology, 2018)
Obstetric complications are an issue of concern in all countries and especially, in developing countries. The prevalence of obstetrics complications measures the development path and the implementation of motherhood initiative 1999 for reducing obstetric complications and maternal mortality. The study aimed at estimating the level and socio-economic causes of obstetric complication in Gezira state. The data source of this research is based on a longitudinal sample of 400 women who were admitted to Wad Medani Obstetrics and Gynecology Hospital. The research used descriptive statistics, cross tabs with chi- square and logistic regression analyses utilizing SPSS program. The main study results include that: the rate of obstetric complications is high in Gezira state amounting to 60 % approximately. The results also indicated that the modal complications are pregnancy induced hypertension, septicemia and placenta previa while the modal problems are malaria and anemia. The study recommended reducing intervention delays by consultants upon admission, abolish unnecessary cesarean sections and women must go to antenatal care clinics according to WHO protocol.